Tuffs, tectonism and glacially related sea-level changes, Carboniferous-Permian, Southern Namibia. - Stollhofen, Harald; Stanistreet, Ian G.; Bangert, Berthold; Grill, Hermann (Palaeogeography, Palaeoclimatology, Palaeoecology, 2000)
The Carboniferous-Permian glacigene Dwyka Group in southern Africa has been widely regarded as amagmatic. Only in the higher parts of the Permian and subsequent younger strata has evidence of magmatism been recognised, particularly in the form of pyroclastic fallout ash beds. The source of these tufts has been suggested to be Patagonia and West Antarctica, forming part of an extensive volcanic arc which lay some 1500 to 2000 km to the south and west in their pre-break-up Gondwana positions. Rhyolitic/dacitic and basaltic/andesitic tuff beds within the glaciomarine sediments of the Dwyka Group in Namibia reveal new evidence for an early onset of proximal bimodal volcanic activity in southern Africa. Contemporaneous tectonism is recorded by type-1 unconformities and systematic thickness changes across NW-SE trending extensional normal faults. We suggest that this tectonomagmatic period marks initial extensional events in southern Namibia and the Carboniferous-Permian volcanic trend appears to coincide with the position of the eventual Namibian continental margin. Significantly, the stratigraphic positions of the tuff beds show a distinct association with enclosing marine transgressive depositional sequences. Most of them coincide with sharply defined flooding surfaces within relatively thick shaly successions, reflecting their multiple transgressive nature. Widening the study context to the latest Early Permian in southern Africa, the main Karoo Basin of southern Africa exhibits a similar coincidence of marine transgressions and extrusion of volcanics. The relationship between tuff beds and transgressive depositional sequences is not only the result of enhanced preservational potential during transgression, but of a genetic coupling between magmatism, extensional tectonics and basin subsidence, the latter accelerating a rise in relative sea-level. This interaction is significant, not only for understanding potential controls on relative sea-level change, but also for understanding the early geodynamic evolution of the southern South Atlantic continental margin. (C) 2000 Elsevier Science B.V.
UnivIS-Import:2015-03-09:Pub.2000.nat.dgeo.IGM.LG.tuffst
Keywords: Dwyka; Glacial; Glacio-eustatic; Gondwana; Karoo; Namibia; Sea-level; Vo lcanism